Some parameters that affect CDMA capacity analysis. Results using GIS based simulation (2001)
In previous papers we describe a model for capacity analysis in CDMA systems using DC-Cell, a GIS based planning tool developed at Universidad Politecnica de Valencia, and MATLAB. We show some initial results of that model, and now, we are exploring different parameters like cell size, proximity between cells, number of cells in the system and “clustering” CDMA in order to improve the planning process for third generation systems. In this paper we show the results for variations of some of these parameters, specifically the cell size and number of cells. In CDMA systems is quite common to suppose only one carrier frequency for capacity estimation, and it is intuitive to think that for more base stations, mean more users. However the multiple access interference problem in CDMA systems could establish a limit for that supposition in a similar way that occurs in FDMA and TDMA systems.